1994
DOI: 10.1126/science.265.5171.512
|View full text |Cite
|
Sign up to set email alerts
|

Creation of Liquid Crystal Waveguides with Scanning Force Microscopy

Abstract: The rubbing of a polymer layer, a commonly applied process, leads to an anisotropic surface morphology, aligning liquid crystal molecules. Scanning force microscopy can be used to intentionally create areas with a similar anisotropy by operating the instrument at loads in the range of 10(-7) to 10(-5) newtons. These areas have an orientation effect on liquid crystals indistinguishable from the rubbing process, which allows a systematic investigation of the orientation properties of an alignment layer as a func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(55 citation statements)
references
References 8 publications
1
54
0
Order By: Relevance
“…According to the elastic continuum theory of Berreman 8 the rubbing induces grooves on the polymer surface and the liquid crystal molecules prefer to align parallel to the direction of the grooves. This explanation was also used by Ruetschi et al 2 Geary et al 9 suggested the alignment of the molecular chains of the polymers by buffing to be responsible for the LC alignment. According to their theory the molecular chains at the surface of the polymer align by the stress that is induced by the rubbing and the LCs will anchor to these aligned chains.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…According to the elastic continuum theory of Berreman 8 the rubbing induces grooves on the polymer surface and the liquid crystal molecules prefer to align parallel to the direction of the grooves. This explanation was also used by Ruetschi et al 2 Geary et al 9 suggested the alignment of the molecular chains of the polymers by buffing to be responsible for the LC alignment. According to their theory the molecular chains at the surface of the polymer align by the stress that is induced by the rubbing and the LCs will anchor to these aligned chains.…”
Section: Introductionmentioning
confidence: 68%
“…However, in the very thin PI films ͑a few nanometers͒ surface interactions fix the polymer chains to the surface. The fixed chains cannot be reoriented by the tip, but rather the tip will break the polymer chain and will produce grooves on the surface similar to those observed by Ruetschi et al 2 As an example of a polymer with different mechanical properties we studied the alignment properties of poly͑m-ethyl metha acrylate͒ ͑PMMA͒. Conventionally rubbed PMMA aligns nematic liquid crystals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism for this phenomenon was proposed in 1971 by Berreman, 15 and probed later using experiments with materials containing topographically anisotropic surfaces. [18][19][20][21][22][23][24] In these cases, the driving force for LC alignment arises mainly from physical interactions between the surface and the LC molecules. The LC director is preferentially aligned along the direction of low roughness so that the total elastic free energy of the LC is minimized.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ruetschi et al 3 showed that the atomic force microscope ͑AFM͒ in contact mode can be used to obtain relatively smooth polymer aligning surfaces with controllable anchoring strengths. 4,6 This alignment method has already been applied to obtain specific configurations of polymer layers, 5 LC gratings, 6 as well as controllable gray scale 7 and bistability 8 properties.…”
Section: Introductionmentioning
confidence: 99%